Activation of CN bonds by high-valent group 6 metal chlorides, including the conversion of an α-diimine into a functionalized imidazolium. (20th April 2018) - Bartalucci, Niccolò; Bortoluzzi, Marco; Zacchini, Stefano; Pampaloni, Guido; Marchetti, Fabio
Abstract : The direct interactions of WCl6 and MoCl5 with α-diimines (and also a carbodiimide in the case of MoCl5 ) have been explored, leading to unusual reaction pathways. Abstract : The α-diimine (Xyl)NCHCHN(Xyl) (DAD Me ; Xyl = 2, 6-C6 H3 Me2 ) was converted by the reaction with WCl6 into the iminomethyl-imidazolium compound [(Xyl)NCHCHN(Xyl)CCHN(Xyl)][WCl6 ], 1, in 47% yield. Mono (N-protonated) α-diimine salts were isolated from the reactions of WCl6 with (2, 6-C6 H3 Et2 )NC(Me)C(Me)N(2, 6-C6 H3 Et2 ) (Me-DAD Et ) and of MoCl5 with (2, 6-C6 H3 Et2 )NCHCHN(2, 6-C6 H3 Et2 ) (DAD Et ) and (2, 6-C6 H3 t Bu2 )NCHCHN(2, 6-C6 H3 t Bu2 ) (DAD t Bu ), giving respectively [(2, 6-C6 H3 Et2 )NHCHCHN(C6 H2 Et2 Me)][WCl6 ], 2 (minor product), [DAD Et (H)]2 [Mo2 Cl10 ], 3a, and [DAD t Bu (H)]2 [Mo2 Cl10 ], 3b . MoCl5 reacted with the carbodiimide (4-C6 H4 Me)NCN(4-C6 H4 Me) affording 70% yield of MoCl4 [(4-C6 H4 Me)NC(Cl)N(4-C6 H4 Me)], 4 . All the products were characterized by analytical and spectroscopic methods, and the X-ray structures of1, 2 and4 were elucidated by X-ray diffraction. DFT calculations were performed to shed light on mechanistic and structural aspects.